Animation of landscape using digital elevation model and satellite dada - Wu, Xiao Wen; Murai, Shunji; Huynh, Ngoc Phien; Yulu, Qi; DAAD (Bangkok : Asian Institute of Technology, 1993)
Animation of bird's eye view becomes more useful for investigating the details of a land of interest from view point of environment, geomorphology, geology, disaster etc. In this study, an animation system using Digital Elevation Model and Satellite images has been proposed and implemented. A fast algorithm for producing three-dimensional perspective view of terrain images has been proposed and proved to be more efficient in the implementation. Two kinds of animate motion are provided in the system: linear and rotation. The fast linear movement is achieved by pre-sorting the image and computing the image movement velocity. A parallel animation system has been experienced under the PVM (Parallel Virtual Machine) environment. A satisfied speedup is obtained as the number of processor increases.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science
Thesis (M.Sc.) - Asian Institute of Technology, 1993
Keywords: Computer animation